2014
DOI: 10.1590/s0103-90162014000200003
|View full text |Cite
|
Sign up to set email alerts
|

Reducing supplementation frequency for Nellore beef steers grazing tropical pastures

Abstract: Reduced supplementation frequency is a broadly applied management practice.Ruminants consuming low quality forages/pastures, supplemented less than once daily are able to maintain body weight gain (BWG), effi ciency of use of dry matter, nitrogen and other nutrients, as compared with animals supplemented once daily. We evaluated the feeding behavior, dry matter intake (DMI), dry matter and organic matter digestibility (DMD and OMD), BWG, Longissimus muscle area and backfat depth of Nellore steers raised on Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
5
0
2
Order By: Relevance
“…The results obtained in the present study agree with those found by other authors who also observed that ruminants grazing low-quality forage and supplemented with high-protein supplements showed similar dry matter intake (DMI) between frequencies of supplementation (infrequently or daily) (Canesin et al, 2007;Morais et al, 2009;Canesin et al, 2014;Morais et al, 2014). Krehbiel et al (1998) showed that DMI and the net portal and hepatic flux of nutrients in mature ewes fed low-quality forage increased in response to supplementation with 80 g CP day -1 of soybean meal, with no differences observed due to the frequency of supplement administration (once daily or every three days).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results obtained in the present study agree with those found by other authors who also observed that ruminants grazing low-quality forage and supplemented with high-protein supplements showed similar dry matter intake (DMI) between frequencies of supplementation (infrequently or daily) (Canesin et al, 2007;Morais et al, 2009;Canesin et al, 2014;Morais et al, 2014). Krehbiel et al (1998) showed that DMI and the net portal and hepatic flux of nutrients in mature ewes fed low-quality forage increased in response to supplementation with 80 g CP day -1 of soybean meal, with no differences observed due to the frequency of supplement administration (once daily or every three days).…”
Section: Discussionsupporting
confidence: 92%
“…The characteristics of structure, biomass availability and forage quality were assessed by throwing five 1 m × 1 m metal squares randomly onto each paddock and cutting forage within them at the ground level. Half of the collected biomass was separated into green leaves, stems and dead material, and the rest was oven-dried (55 °C) for chemical composition and alkane analysis (Table 2) (Morais et al, 2009;Canesin et al, 2014;Morais et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Benatti et al (2012) and Canesin et al (2014) also found the same time expended on the grazing activity (considering the average of two days of evaluation) when comparing supplementation provided daily vs. three times weekly.…”
Section: Resultsmentioning
confidence: 74%
“…Em tal condição, os bovinos são submetidos a carências nutricionais múltiplas e a proteína (compostos nitrogenados) assume papel prioritário, uma vez que o alimento disponível ou a reciclagem endógena de nitrogênio não atende aos requerimentos microbianos, incorrendo em limitação no crescimento e na atividade dos mesmos, bem como queda na digestibilidade da parede celular, o que acarreta em diminuição do consumo de forragem e do desempenho animal (HERSOM, 2008;CAPPELLOZZA et al, 2013). A suplementação de bovinos em pastagem tem como objetivos cobrir deficiências dietéticas das forragens e permitir ao animal aumentar o consumo de nutrientes digestíveis, aumentando o desempenho, aumentar o retorno econômico e manejar o comportamento do gado (KUNKLE et al, 2000;SILVA et al, 2010;MATEUS et al, 2011;CANESIN et al, 2014). Nesse contexto, a suplementação com fontes de proteína de alta degradabilidade ruminal, ou nitrogênio não proteico como a uréia, para animais em pastejo promove aumento na síntese microbiana e na taxa de passagem, resultando na elevação do consumo de forragem (MOORE et al, 1999;McGUIRE et al, 2013).…”
Section: Introductionunclassified
“…Em virtude do baixo teor de proteína presente no pasto (cerca de 2%), a proteína para ganho foi oriunda do suplemento. Apesar do SP apresentar 70% de PB, entre consumo de pasto, estimado em 1% do PC, e de suplementos, resultaria em proporções inferiores a 7% de PB, mínimo recomendado na literatura (McGUIRE et al, 2013;CANESIN et al, 2014), em virtude do baixo consumo do suplemento. Portanto, fontes de proteína verdadeira e energia devem estar presentes nos suplementos.…”
Section: Introductionunclassified